Media Utilization in Children’s Mathematics Learning Early Childhood Math Learning from the Parent’s Perspective: an Overview of Learning from Home (BDR) Conditions During the Pandemic - Herwina Dewi Librianty; Yennizar N; Roficha Yuliani (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
The use of media in learning mathematics for early childhood is a virtue that aims to make it easier for children to understand concepts while at the same time attracting children to participate. For ECE teachers the provision and use of media in learning is a common thing, it has even become their mandatory routine. However, for parents the strategy of using media in learning mathematics for early childhood is something they do not fully understand. Especially during difficult conditions where parents are the main responsible for the success of learning carried out at home during the pandemic. This study aims to describe parents' perceptions of strategies for using media in early childhood mathematics learning when learning from home during a pandemic. This study used a quantitative approach in the nature of survey research by distributing questionnaires to 52 parents at Al-Hidayah Terentang Baru Kindergarten, Bathin District, Batanghari Regency. Obtaining data based on questionnaire answers was then analyzed descriptively quantitatively in the form of a histogram and interpretation was carried out and the percentage was measured. The results show that 88% of parents perceive that the strategy of using media in learning mathematics, especially during BDR/Learn From Home, is very important because it facilitates the process of absorbing subject matter as well as being fun for children. This process of course also requires coordination and collaboration between parents and teachers in the Education Unit. Therefore, it can be concluded that the understanding of parents, especially in Al-Hidayah Kindergarten in Terentang Baru Village, on the importance of optimizing the quality of learning through strategies for using media in learning mathematics for early childhood during the pandemic is quite good.